Features of investment in human capital - Mamych, Andriy (Management and Entrepreneurship: Trends of Development, 2017)
The relevance of the research is determined by a total necessity disclosure of the nature and level of investment in human capital in view of the crucial role of intellectual abilities in the global economy. The subject of the study is theoretical and methodological foundations of human capital and applied aspects of formation and strategies invested. Problem setting. Theoretical and practical analysis of the significance for enterprises and states in general of human capital and its investment is crucial for further scientific study of the issue, and so for the practical implementation of the theoretical achievements of the study to provide the growth of economic indicators of all stakeholders. Purpose. Study on the importance of human capital and its development on the efficiency of enterprises and increase national income. The general paper objective is to demonstrate the importance of human capital in the development of enterprises and the country. The specific paper objectives are: to demonstrate the importance of investment in human capital and create a scientific basis for further study of the issues of development of the human capital; to show the interdependence of human capital and economic indicators and provide recommendations on their improvement in Ukraine Design/methodology/approach. Historical, analytical and comparative methods used by the system and structural and functional approaches. Findings. Recommendations are made on the establishment of a policy for the development of human resources and capacity. Analysis of recent studies and publications dedicated to the issue, as evidenced by the vastness of the literature on the subject: author’s books and articles in economics, the works of political thinkers, dissertations and original publications on economics. The leading economists have been interested in the issue of human capital since the last centure. T. Schulz, H. Becker, E. Denison, D. Mintser and others studied various aspects of the relevance of human capital, which influences the effectiveness in their works. However, the most of scientists focused on the analysis and the determination of the qualifying features of work force. At the same time, the issues of education and learning have not been investigated. Accordingly, the subject requires more research, considering its urgent importance. Research limitations/implications. The paper studies the results caused by investments in human capital, which play a large role in the development of the economy. Investments in human capital have features that distinguish them from other types of investments. The nature, extent and types of investment in people are determined by historical, national, cultural characteristics and traditions of society, the mentality of the people. For example, education and career choices of children largely depend on family traditions, occupation and education level of their parents. When investor allocates his capital, he expects to receive the projected socio-economic benefit in the nearest future. The full effect can be expected only if the problems of investing in human capital, such as a high degree of risk are minimized. Another equally serious and important problem is the difficulty in determining the effectiveness of investments: there are different approaches to evaluating the effectiveness of investments in human capital. As you know, the investment in human capital can be performed by not only companies and organizations, but also by the state and its effectiveness is determined by Human Development Index. Ukraine ranks 81 in the list but it can enhance rank through continuous education. Originality/value. Such knowledge will help to the growth of economic indicators of both owners of enterprises and national income in general. Potential development of any country depends on human capital. Since the considered and consistent policy on human resource development and balanced investment in human capital at the level of individual firms, and in general at the national level are required. Moreover, if Ukraine wants to enter the path of high economic growth, it needs to review state measures to increase the investment factor of human capital, which will increase not only productivity, but also a number of indicators of the national economy, which will contribute to its growth